Determination of Trifluoroacetic Acid and Chloride in Celecoxib Drug - Chen, Meilan; Ye, Mingli; Hu, Zhongyang; Pan, Guangwen; Wang, Nani (Asian Journal of Chemistry, 2014)
A method for the determination of trifluoroacetic acid and chloride in celecoxib drug by valve switching-ion chromatography was developed. Chromatographic separation was performed on an IonPac AS23 column. Mixture of 3.5 mmol/L sodium carbonate and 1.4 mmol/L sodium bicarbonate was used as mobile phase. Since celecoxib is poorly water-soluble (0.007 mg/mL), but extremely soluble in methanol (113.94mg/mL). Ion chromatographic columns are prone to fouling by strongly-retained organic sample components. In our research, column contamination caused by the drug molecule and organic solvent was avoided by using a valve-switching sample preparation method. The linear ranges of the method for the two analytes were 0.10-10 μg/mL and the detection limits (S/N = 3) of trifluoroacetic acid and chloride were 0.06 and 0.006 mg/L, respectively. This method was successfully applied to the determination of trifluoroacetic acid and chloride in real samples. The spiking recoveries of trifluoroacetic acid and chloride were in the range of 90 to 94 %.